Applying Problem-Based Learning and Drill Method to Enhance Critical Thinking and Learning Outcomes - Royu Lumbansiantar (Soedirman Economics Education Journal, 2025)
Critical thinking skills and learning outcomes are two important aspects that are interrelated in achieving optimal learning objectives. This study aims to describe the effectiveness of the application of the Problem Based Learning (PBL) learning model combined with the drill method in improving students' critical thinking skills and learning outcomes in the material of trading company financial reports. This study uses a classroom action research (CAR) approach which is implemented in two cycles. Each cycle consists of two meetings that include the stages of planning, action implementation, observation, and reflection. The subjects in this study were 29 students of class XI Accounting 3 SMKN 1 Nainggolan. Data collection techniques were carried out through observation, learning outcome tests, and documentation. The results showed that students' critical thinking skills increased from an average of 58.76% in cycle I to 72.70% in cycle II. Meanwhile, the level of completion of learning outcomes classically increased from 79.31% in cycle I to 100% in cycle II. Thus, it can be concluded that the application of the Problem Based Learning model with the drill method is effective in improving students' critical thinking skills and learning outcomes.